Pengujian dan Perawatan Sistem Penghitung Jumlah Mahasiswa Aktif Jurusan Ilmu Komputer - Dwi Sakethi; Didik Kurniawan; Hartanto Tantriawan (Universitas Lampung, 2014)
Active student of computer science system is a system developed based on academic information system (siakad) which is managed by The University of Lampung. The system is built to calculate the number of active students based on data that has been inputted by students into the KRS at the beginning of the semester. KRS data is used to build the system to calculate the number of active students majoring in Computer science. The system was developed using PHP and MySQL, and tested using the Black box and White box testing.